Toward Evidence-Based Practice. Issue 6 (November 2020) - Rohan, Annie J.; Adams, Ellise D.; Eaton, Carrie M.; Hayman, Laura L.
Abstract : Experts suggest how 6 research articles can be used in nursing practice.